Encuesta serológica de parvovirus en cerdos no vacunados y sacrificados en el matadero de Turbo (1999)
ABSTRACT: In this study were determined the levels of antibodies to the porcine parvovirus in 87 animals sacrificed in Turbo (Antioquia). A percentage of positive and negative reactors of the 49.42% was obtained (43/87) respectively. The percentage of titles of positive antibodies were of 65.9% (29/44) for the male, and 32.6% (14/43) for the females. By means of the statistical test of independence was high relationship between the sex variable and positive, it refuse the null hypothesis with a level of probability of 5%